(untitled) (Papeles, 2022)
The use of native plants in food is a traditional practice that, in many territories, has been abandoned or modified. The Convention on Biological Diversity establishes the protection of customary use of biological resources, in accordance with traditional cultural practices (art. 10 CBD). This paper describes and analyzes the traditional food practices with native plants in two localities of Entre Ríos: Las Cuevas and Nogoyá. The cultural changes that have occurred in recent decades in these localities show an increase in urbanization coupled with internal migration, changes in land use, lack of subjective appropriation of traditional knowledge and a limitation of the food repertoire. Based on the analysis of information obtained from interviews and workshops, we describe the food practices that incorporated native plants and that are no longer maintained, either due to cultural changes or to the difficulty of accessing these biological resources. The legislation is also examined to identify the absence of the category of native or wild plants in our legal system. Since this knowledge has not been codified for academic transmission, this prevents its inclusion in formal education.